Probing elementary steps under reaction conditions using infrared spectroscopy - Stacchiola, Dario; Calaza, Florencia; Burkholder, Luke; Schwabacher, Alan; Neurock, Matthew; Tysoe, Wilfred (Ciencia, 1970)
The reaction pathway for the palladium-catalyzed synthesis of vinyl acetate from acetic acid, ethylene and oxygen is investigated using reflection-absorption infrared spectroscopy by monitoring the rate of acetate titration by gas-phase ethylene. This reveals that acetate species are removed by reaction with gas-phase ethylene resulting in vinyl acetate formation. Reaction with C2D4 reveals a large (ï¾6) isotope effect indicating that hydrogen is involved in the rate-limiting step. This also results in the appearance of an infrared feature that is assigned to an acetoxyethyl- palladium intermediate. Acetate reaction rates are different for the isotopomers, CH2CD2 and CHDCHD. These observations are consistent with a reaction pathway first proposed by Samanos in which ethylene reacts with an acetate species to form an acetoxyethyl-palladium intermediate, which then reacts to form vinyl acetate by a ï¢-hydride elimination reaction.